Perbedaan Saturasi Oksigen dan Denyut Jantung Bayi Sebelum dan Sesudah Diberikan Posisi Semipronasi dengan Nesting pada Bayi Berat Lahir Rendah di RSUD Kabupaten Temanggung: Differences In Oxygen Saturation And Heart Rate Of Babies Before And After Semipronation With Nesting Position In Low Birth Weight Babies At General Hospital of Temanggung - Sri Witartiningsih; Umi Aniroh (Journal of Holistics and Health Sciences (JHHS), 2022)
Babies with low birth weight (LBW) are a problem that needs attention, because they have a high risk of morbidity and mortality, so special care is needed such as by providing the right position. Position of semi-pronation with nesting is an important intervention for optimizing the function of the organ systems in low birth weight babies. Based on data at the General Hospital of Temanggung in 2019, from 1083 births of babies, 257 were born with low birth weight or 23.73%. The objective of this study was to determine the differences in oxygen saturation and heart rate of babies before and after being given a semi-pronation position with nesting in low birth weight babies at the General Hospital of Temanggung. The research used a quantitative approach, the method used in this study was pre-experiment. The design used in this study was One Group pretest-posttest design. The population was all LBW in General Hospital of Temanggung with accidental sampling technique with a sample size of 20 respondents. The research measurement tool used a checklist. The data analysis used was the Wilcoxon-test. The average oxygen saturation is 94.40% and the heart rate is 127.20 x/minute before giving the semipronation position with nesting, while the average oxygen saturation is 98.15% and the heart rate is 143.50 after giving the semipronation position with nesting. There is a difference in oxygen saturation (p-value 0,000 and Z- score 4,308) and heart rate (p- value 0,001) of babies before and after being given a semipronation position with nesting in Low Birth Weight Babies at the General Hospital of Temanggung. Giving a semipronation position with nesting can be used as an intervention to improve the physiological response of babies, especially on oxygen saturation and heart rate in low birth weight babies. ABSTRAK Bayi dengan Bayi Berat Lahir Rendah (BBLR) merupakan masalah yang perlu mendapat perhatian, karena memiliki resiko morbiditas dan mortalitas yang tinggi, sehingga perlu dilakukan perawatan khusus seperti dengan memberikan posisi yang tepat. Pemberian posisi semipronasi dengan nesting merupakan intervensi yang penting bagi optimalisasi fungsi sistem organ pada bayi berat lahir rendah. Berdasarkan data di RSUD Temanggung pada tahun 2019 dari 1083 kelahiran bayi, 257 kelahiran dengan BBLR atau sebesar 23,73%. Tujuan dari penelitian ini untuk mengetahui perbedaan saturasi oksigen dan denyut jantung bayi sebelum dan sesudah diberikan posisi semipronasi dengan nesting pada bayi berat lahir rendah di RSUD Kabupaten Temanggung. Penelitian ini menggunakan pendekatan kuantitatif, metode yang digunakan dalam penelitian ini adalah pre-experiment. Desain yang digunakan dalam penelitian ini One Group pretest-posttest design. Populasi adalah semua BBLR di RSUD Temanggung dengan teknik accidental sampling dengan jumlah sampel yaitu 20 responden. Alat ukur penelitian menggunakan checklist. Analisa data yang digunakan adalah uji Wilcoxon. Rata-rata saturasi oksigen 94,40% dan frekuensi denyut jantung 127,20 x/menit sebelum dilakukan pemberian posisi semipronasi dengan nesting, sedangkan rata-rata saturasi oksigen 98,15% dan frekuensi denyut jantung 143,50 sesudah dilakukan pemberian posisi semipronasi dengan nesting . Ada perbedaan saturasi oksigen (p value 0,000 dan Z- Score 4,308) dan denyut jantung (p- value 0,001) bayi sebelum dan sesudah diberikan posisi semipronasi dengan nesting pada Bayi Berat Lahir Rendah di RSUD Kabupaten Temanggung. Pemberian posisi semipronasi dengan nesting dapat dijadikan sebagai intervensi untuk meningkatkan respon fisiologi bayi terutama pada saturasi oksigen dan frekuensi denyut jantung pada bayi berat lahir rendah.